2015
DOI: 10.1071/wr15064
|View full text |Cite
|
Sign up to set email alerts
|

Mixed stock analysis of a resident green turtle, Chelonia mydas, population in New Caledonia links rookeries in the South Pacific

Abstract: Context Migratory species are known to pose a challenge for conservation because it is essential to understand their complex life history in order to implement efficient conservation actions. Aims In New Caledonia, large seagrass habitats in the Grand Lagon Sud (GLS) are home to resident green turtles (Chelonia mydas) of unknown origins. To assess the stock composition in the GLS, 164 foraging turtles were sampled for genetic analysis of ~770 base pairs of the mitochondrial DNA (mtDNA) control region. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…In addition, we increased the sample size from some rookeries and included samples from 3 new rookeries: Browse Island in Western Australia, Cocos (Keeling) Island, and Cobourg Peninsula in the Northern Territory. We also used data from the published literature for rookeries in Palau, Yap, Northern Mariana Islands, Guam, Marshall Islands, American Samoa, New Caledonia and French Polynesia (Dutton et al 2014) as well as additional samples from New Caledonia, the Chesterfield Islands and Vanuatu (Read et al 2015). Additional samples from 32 nesting females collected from Raine Island (nGBR) in 2008 were analysed to assess whether there was temporal variability in the genetic structure of the nGBR nesting population (Table S1 in the Supplement at www.int-res.com/ articles/ suppl/ m543 p241 _supp.xlsx).…”
Section: Sample Collectionmentioning
confidence: 99%
“…In addition, we increased the sample size from some rookeries and included samples from 3 new rookeries: Browse Island in Western Australia, Cocos (Keeling) Island, and Cobourg Peninsula in the Northern Territory. We also used data from the published literature for rookeries in Palau, Yap, Northern Mariana Islands, Guam, Marshall Islands, American Samoa, New Caledonia and French Polynesia (Dutton et al 2014) as well as additional samples from New Caledonia, the Chesterfield Islands and Vanuatu (Read et al 2015). Additional samples from 32 nesting females collected from Raine Island (nGBR) in 2008 were analysed to assess whether there was temporal variability in the genetic structure of the nGBR nesting population (Table S1 in the Supplement at www.int-res.com/ articles/ suppl/ m543 p241 _supp.xlsx).…”
Section: Sample Collectionmentioning
confidence: 99%
“…The maternally inherited mitochondrial (mt)DNA control region sequences have been used extensively in sea turtles [21], and elucidate the connectivity between nesting and foraging areas [22,23]. When the genetic stock structure of breeding populations are known (and sufficiently differentiated), they can be used as a reference to trace back the natal origin of turtles using a mixed stock analysis (MSA) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown considerable variation in results, with some foraging ground aggregations being composed mostly of turtles from the nearest stock (see Glossary) such as Hawaii, Aru, Gulf of Carpentaria, and the northern and southern Great Barrier Reef Dethmers et al, 2010;Jensen et al, 2016a), while other aggregations include significant numbers of turtles from distant stocks over 2,000 km away such as Palmyra, New Caledonia, Colombia and Japan (Amorocho et al, 2012;Nishizawa et al, 2013;Naro-Maciel et al, 2014b;Read et al, 2015). A similar pattern is evident in the Atlantic basin where transatlantic dispersal has been identified from Suriname to the West coast of Africa and from rookeries in western Africa to the Brazilian coast (Monzón-Argüello et al, 2010).…”
Section: Green Turtle Habitat Connectivity: Which Nesting Stocks Use mentioning
confidence: 99%
“…Since then, studies including additional beaches in Taiwan (Cheng et al, 2008) and Japan (Nishizawa et al, 2011;Hamabata et al, 2013) have shown population differentiation between rookeries separated by no more than 150 km, identifying six new MUs in the Northwest Pacific. Recent regional analyses of Southwest and South-central Pacific green turtle rookeries also filled a significant gap across a large portion of the western Pacific and identified seven MUs Read et al, 2015). In contrast, in the central and eastern Pacific only five MUs have been identified, with no genetic differentiation detected between neighboring rookeries in the Hawaiian archipelago (>500 km), the Revillagigedo Islands (∼400 km), or between rookeries in the Galapagos and mainland Ecuador (>1,000 km) (Dutton et al, 2014a;Chaves et al, 2017).…”
Section: How Are Rookeries Connected To Each Other and Linked To Foramentioning
confidence: 99%
See 1 more Smart Citation